Agglomeration-free nanoscale TiC reinforced titanium matrix composites achieved by in-situ laser additive manufacturing. (October 2020) - Wei, Wenhou; Zhang, Qi; Wu, Wenjie; Cao, Hongzhong; Shen, Jun; Fan, Shuqian; Duan, Xuanming
Abstract: A novel laser additive manufacturing method is proposed to manufacture the agglomeration-free nanoscale TiC-reinforced titanium-matrix composites by in-situ compounding the reinforcement via gas–liquid reaction. The clean interface and strong interfacial bonding between the in-situ nanoscale TiC reinforcement and the matrix alloy can significantly improve grain boundary behavior and grain boundary strength, besides, the mechanisms of achieving simultaneously high strength and high plasticity in the TiC/Ti6Al4V composites were studied. The proposed in-situ additive manufacturing method using pyrolysis-reaction would open a new route for manufacturing of the homogeneous and agglomeration-free nanocomposites parts with high-complexed structures and excellent mechanical properties. Graphical abstract: Image, graphical abstract